2019
DOI: 10.1177/1971400919870180
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of the dentato-rubro-thalamic tract for MR-guided focused ultrasound treatment of essential tremor

Abstract: Background Magnetic resonance-guided focused ultrasound ablation of the thalamic ventral intermediate nucleus is a safe and effective treatment for medically refractory essential tremor. However, indirect targeting of the ventral intermediate nucleus using stereotactic coordinates from normal neuroanatomy can be inefficient. We therefore evaluated the feasibility of supplementing this method with direct targeting of the dentato-rubro-thalamic tract. Methods We retrospectively identified four patients undergoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 30 publications
2
28
0
Order By: Relevance
“…Additionally, we performed searches on PubMed Central with the key terms "Tremor AND Tractography AND Focused Ultrasound" on March 9, 2020, which were similarly screened. These search terms identified 56 unique articles in the English language, 9 of which described case reports or studies utilizing tractography to facilitate targeting of either DBS 13,[17][18][19][20] or MRgFUS, [21][22][23] with 3 additional references found on cross-referencing. 15,24,25 The full text was screened to characterize the tractography methodology and report of clinical outcomes.…”
Section: Tractography For Direct Vim Targeting For Dbs or Mrgfusmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, we performed searches on PubMed Central with the key terms "Tremor AND Tractography AND Focused Ultrasound" on March 9, 2020, which were similarly screened. These search terms identified 56 unique articles in the English language, 9 of which described case reports or studies utilizing tractography to facilitate targeting of either DBS 13,[17][18][19][20] or MRgFUS, [21][22][23] with 3 additional references found on cross-referencing. 15,24,25 The full text was screened to characterize the tractography methodology and report of clinical outcomes.…”
Section: Tractography For Direct Vim Targeting For Dbs or Mrgfusmentioning
confidence: 99%
“…Finally, Miller et al reported substantial tremor reduction in 4 patients undergoing unilateral MRgFUS at the AC-PC level, defining targets with a combination of coordinates and 1-tract approach. 23 Overall, several tractography approaches are feasible. These prior reports have included both deterministic 19,22,23,25,26,28 and less commonly probabilistic 15 approaches for targeting.…”
Section: Tractography For Direct Vim Targeting For Dbs or Mrgfusmentioning
confidence: 99%
See 1 more Smart Citation
“…Much recent work has investigated personalized Vim targeting through the use of connectivity‐derived definitions of the Vim, primarily based on DTI. These DTI‐based approaches include identifying the Vim based on its known connection with the dentato‐rubro‐thalamic tract (Chazen et al, 2018; Coenen et al, 2017; Fenoy & Schiess, 2017, 2018; King et al, 2017; Low et al, 2019; Miller et al, 2019; Morishita et al, 2019; Sammartino et al, 2016; Sasada et al, 2017) or bounding fiber bundles (Krishna et al, 2019; Ranjan et al, 2019) or by segmenting the thalamus based on connectivity with the cerebral cortex (Akram et al, 2018; Middlebrooks et al, 2018; Pouratian et al, 2011; Tian et al, 2018; Tsolaki, Downes, Speier, Elias, & Pouratian, 2018). There is accumulating evidence that this connectivity‐based targeting provides an individualized initial targeting method associated with good clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…However, there has also been debate as to which seed regions of interest to use for DTI, technical difficulties associated with DTI for the thalamus, and differences across studies on the precise “sweet spot” within the Vim to target, making the optimal connectivity‐based targeting method still an open question (Akram et al, 2019; Middlebrooks et al, 2019). Thus far, the leading definition of the sweet spot is the thalamic region intersecting with the dentato‐rubro‐thalamic tract (Calabrese et al, 2015; Akram et al, 2018; Chazen et al, 2018; Fenoy & Schiess, 2017, 2018; Weidman, Kaplitt, Strybing, & Chazen, 2019; Morishita et al, 2019; Low et al, 2019; Miller et al, 2019; but see Schlaier et al, 2015). Additional reported sweet spots across the literature include thalamic regions connected with M1, SMA, or premotor cortex (Akram et al, 2018; Middlebrooks et al, 2018; Pouratian et al, 2011; Tsolaki et al, 2018), and near the inferior and posterior boundary of the Vim (Al‐Fatly et al, 2019; Atkinson et al, 2002; Boutet et al, 2018).…”
Section: Discussionmentioning
confidence: 99%